The Effectiveness of Small-Sided Games in Enhancing Technical Skills and Physical Fitness among Adolescent Football Players - Fajri Hamzah; Ahmad Syarif Burhan; Binsar Hasudungan Sihombing; Rachmat Hidayat; Irsan Kahar (CV Lentera Cendekia Indonesia, 2025)
Purpose: This study aimed to examine the effectiveness of Small-Sided Games (SSGs) in improving technical skills and physical fitness among adolescent football players. Methods: A quasi-experimental design with pre-test and post-test measurements was conducted on 30 male football players aged 13–15 years. The participants underwent an eight-week SSG training program, held three times per week. Technical skills were assessed through passing accuracy, dribbling time, and shooting accuracy tests, while physical fitness was measured using the Yo-Yo Intermittent Recovery Test Level 1, Illinois Agility Test, and Vertical Jump Test. Data were analyzed using paired sample t-tests with a significance level of p < 0.05. Results: Significant improvements were found in all measured variables. Technical performance showed increases in passing (from 15.3 to 18.6 passes), shooting accuracy (12.6 to 16.1 goals), and reduced dribbling time (from 11.2 to 9.8 seconds). Physical fitness indicators also improved, with increases in Yo-Yo IR1 distance (980 m to 1185 m), vertical jump height (39.2 cm to 43.5 cm), and faster agility performance (from 18.5 to 17.2 seconds). Conclusion: Small-Sided Games are an effective and efficient training method for enhancing both technical and physical performance in adolescent football players. Their game-based structure offers a valuable approach to youth football development, combining skill acquisition and conditioning in a realistic and engaging format.